Community pharmacists’ attitudes toward palliative care: An Australian nationwide survey - O'Connor, Moira; Hewitt, Lauren; Tuffin, P. (Mary Ann Liebert, Inc Publishers, 2013)
Background: Pharmacists are among the most accessible health care professionals in the community, yet are often not involved in community palliative care teams.Objective: We investigated community pharmacists’ attitudes, beliefs, feelings, and knowledge about palliative care as a first step towards determining how best to facilitate the inclusion of community pharmacists on the palliative care team.Method: A cross-sectional descriptive survey design was used.Subjects: Community pharmacists around Australia were invited to participate; 250 completed surveys were returned.Measurements: A survey was constructed to measure pharmacists’ knowledge and experience, emotions and beliefs about palliative care.Results: Pharmacists were generally positive about providing services and supports for palliative care patients, yet they also reported negative beliefs and emotions about palliative care. In addition, pharmacists had good knowledge of some aspects of palliative care, but misconceptions about other aspects. Pharmacists’ beliefs and knowledge about palliative care predicted—and therefore underpinned—a positive attitude towards palliative care and the provision of services and supports for palliative care patients.Conclusion: The results provide evidence that pharmacists need training and support to facilitate their involvement in providing services and supports for palliative care patients, and highlight areas that training and support initiatives should focus on.